Dimethyl Fumarate Delays Multiple Sclerosis in Radiologically Isolated Syndrome. Issue 3 (10th December 2022) - Okuda, Darin T.; Kantarci, Orhun; Lebrun‐Frénay, Christine; Sormani, Maria Pia; Azevedo, Christina J.; Bovis, Francesca; Hua, Le H.; Amezcua, Lilyana; Mowry, Ellen M.; Hotermans, Christophe; Mendoza, Jason; Walsh, John S.; et al.
Abstract : Objective: The radiologically isolated syndrome (RIS) represents the earliest detectable pre‐clinical phase of multiple sclerosis (MS). This study evaluated the impact of therapeutic intervention in preventing first symptom manifestation at this stage in the disease spectrum. Methods: We conducted a multi‐center, randomized, double‐blinded, placebo‐controlled study involving people with RIS. Individuals without clinical symptoms typical of MS but with incidental brain MRI anomalies consistent with central nervous system (CNS) demyelination were included. Within 12 MS centers in the United States, participants were randomly assigned 1:1 to oral dimethyl fumarate (DMF) 240 mg twice daily or placebo. The primary endpoint was the time to onset of clinical symptoms attributable to a CNS demyelinating event within a follow‐up period of 96 weeks. An intention‐to‐treat analysis was applied to all participating individuals in the primary and safety investigations. The study is registered at ClinicalTrials.gov, NCT02739542 (ARISE). Results: Participants from 12 centers were recruited from March 9, 2016, to October 31, 2019, with 44 people randomized to dimethyl fumarate and 43 to placebo. Following DMF treatment, the risk of a first clinical demyelinating event during the 96‐week study period was highly reduced in the unadjusted Cox proportional‐hazards regression model (hazard ratio [HR] = 0.18, 95% confidence interval [CI] = 0.05–0.63, p = 0.007). More moderate adverse reactions were present in the DMF (34 [32%]) than placebo groups (19 [21%]) but severe events were similar (DMF, 3 [5%]; placebo, 4 [9%]). Interpretation: This is the first randomized clinical trial demonstrating the benefit of a disease‐modifying therapy in preventing a first acute clinical event in people with RIS. ANN NEUROL 2023;93:604–614 Abstract : This multi‐center, randomized, double‐blinded trial by Okuda, et al. assessed the impact of dimethyl fumarate (DMF) in the time to onset of first clinical symptoms attributable to a central nervous system (CNS) demyelinating event within a follow‐up period of 96 weeks. Treatment with DMF resulted in over 80% risk reduction relative to placebo in the prevention of a first acute clinical event related to multiple sclerosis. A significant reduction in new and/or newly‐enlarging T2‐weighted hyperintense lesions was also observed.